Knowledge Society Discourse in Internationalisation of Higher Education: case study in Governmentality - Terhi Nokkala (Universidad Nacional de Educación a Distancia (UNED), 2006)
This paper discusses the ways in which university and national levelactors in Finland and the Netherlands articulate the dominant knowledge society discourse in their understandings of internationalisation of higher education. This paper argues that the knowledge society discourse producesa dominant political rationality through which universities are governed and govern themselves. In the context of internationalisation of higher education, this discourse is articulated in terms of the competitiveness of the universities and the international skills of the individuals as being the main aims of internationalisation and as main attributes of internationality. The rationality provided by the knowledge society discourse contributes on the one hand to creating universities as enterprising, autonomous, competing actors in theglobal labour and education market, and on the other hand continue to tightly connected them to the project of national competitiveness in the era of globalisation. Este trabajo analiza las maneras bajo las cuales la universidad y otros elementos a nivel nacional en Finlandia y los Países Bajos, articulan el dominante discurso de la sociedad del conocimiento en su comprensión de la internacionalización de la educación superior. Se argumenta que el discurso de la sociedad del conocimiento, produce una racionalidad política a través de la cual las universidades son regidas y se rigen a sí mismas. En el contexto de la internacionalización de la educación superior, este discurso se articula en términos de competitividad de las universidades y las habilidades universales del individuo, siendo ambas categorías los objetivos principales de la internacionalización y el mayor atributo de la internacionalidad. La racionalidad proporcionada por el discurso de la sociedad del conocimiento contribuye, por un lado, a la creación de universidades emprendedoras, autónomas, elementos competentes en el mercado global y educativo. Por otro lado, continúa agrupándolas fuertemente al proyecto de competitividad nacional en la era de la globalización